SYNTHESIS AND INVESTIGATION OF A Zn(II) COMPLEX COMPOUND WITH INDOLE-3-ACETIC ACID AND ACETAMIDE - Ismailova , Shahla; Ibragimov , Sapajan; Soporboev , Zokirjon; Khudoyberganov , Oybek (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The article describes the synthesis of a new mixed-ligand coordination compound of zinc(II) ion with indole-3-acetic acid (heteroauxin) and acetamide. The composition and structure of the obtained complex compound were investigated using elemental analysis and IR spectroscopy. Analysis of the IR spectra allowed determining the coordination modes of the ligands to the metal ion. In the second part of the study, the electronic structure and thermodynamic characteristics of the complex were analyzed using quantum-chemical calculations (DFT method). The results show a high correlation between theoretical and experimental data, providing a basis for the potential biological activity of the synthesized complex.